Customers’ switching intention from Shopee to Tiktok in Jakarta, Indonesia - Rachmakinanti, Cut Azaria Salsabilla; Lavenia, Lavenia; Dwihartanti, Sylvia; Justianto, Jerry S. (International Journal Labs, 2024)
This study uses a quantitative design and purposive sampling. This study uses a quantitative design and purposive sampling technique to investigate the influence of Push-Pull-Mooring (PPM) factors on customer intentions to switch from Shopee to TikTok, two popular shopping platforms in Indonesia. Variables were measured using a 6-point Likert scale, and data were analyzed using SEM PLS version 4. This study found no significant effect of push, pull, and mooring factors on the intention of Indonesian buyers to switch from Shopee to TikTok. However, the study found a link between switching intentions and actual behavior, suggesting that Indonesian customers' platform switching dynamics differ from other countries. Future research needs to explore other factors that affect the desire to switch and investigate the variables affected by push, pull, and mooring factors. It would also be useful to consider other methods for measuring intention to switch between e-commerce and social commerce and expand the study to include all e-commerce applications in Indonesia or other topics.